A Layered Polydiacetylene Containing Hydrogen‐Bonding 4, 4′‐Bipyridyl Guests: Reversible Color Changes with a Wide‐Range Temperature Response. Issue 12 (8th November 2021) - Mochizuki, Yuki; Imai, Hiroaki; Oaki, Yuya
Abstract: Invited for this month's cover is the group of Prof. Yuya Oaki, Keio University, Japan. The cover picture shows a layered polydiacetylene containing hydrogen‐bonding 4, 4′‐bipyridyl guests formed through self‐organization. In classical intercalation chemistry, the interlayer guests are intercalated in the host layers via rigid strong electrostatic interaction. The weaker interlayer interaction via hydrogen bond promotes the dynamic motion directing the thermoresponsive color changes in a wide temperature range. More information can be found in the Full Paper by Yuya Oaki, and co‐workers . Abstract : "A soft layered material was obtained by intercalation of hydrogen‐bonding guests in the layered polydiacetylene (PDA). Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.202100300 ).